2021
DOI: 10.31803/tg-20210429130302
|View full text |Cite
|
Sign up to set email alerts
|

Trading Application Based on Blockchain Technology

Abstract: Blockchain is a growing distributed list of records that are linked using cryptographic hashes. Its robustness, simplicity, immutability and trust are basis for development of interesting innovative business solutions. Considering some use-case scenarios within the financial sector, we developed a Blockchain based trading application placed on the Cosmos network. Cosmos is a decentralized network of independent, scalable, and interoperable Blockchains, creating the foundation for new economy. Our work describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In recent years, many scholars have conducted in-depth research on blockchain technology and self-employment in the construction machinery industry, and have achieved good results. For example, researchers such as Kanevche J used a blockchain federation-backed fog layer and smart contracts to ensure privacy, using optimised smart contracts that reduce the monetary cost of vehicles and provide more location privacy protection; performance analysis showed that the solution provides optimal monetary cost management and secure, private, and fast block validation [8]. sitnik A A by consulting with participating food subsidy various stakeholders in the value chain, proposed a blockchain-based system using the principles of value-focused thinking (VFT), which was demonstrated through a prototype to provide a solution to the food problem [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have conducted in-depth research on blockchain technology and self-employment in the construction machinery industry, and have achieved good results. For example, researchers such as Kanevche J used a blockchain federation-backed fog layer and smart contracts to ensure privacy, using optimised smart contracts that reduce the monetary cost of vehicles and provide more location privacy protection; performance analysis showed that the solution provides optimal monetary cost management and secure, private, and fast block validation [8]. sitnik A A by consulting with participating food subsidy various stakeholders in the value chain, proposed a blockchain-based system using the principles of value-focused thinking (VFT), which was demonstrated through a prototype to provide a solution to the food problem [9].…”
Section: Introductionmentioning
confidence: 99%